Performance of Rainfed Farming Systems in Selected Districts of Southern India - G.R. Desai; P.L. Manohari; S.V. Ramana Rao (Journal of Agricultural Extension Management, 2025)
Rainfed agro eco-system occupies a significant place in Indian Agriculture, covering 96 mha. Which is about 66 per cent of the net cultivated area. This area supports 40 per cent of the country’s human population, 60 per cent livestock population and contributes 44 per cent to the food basket. As such, rain fed farming is found to be the key for future development of agriculture in the country